Penggunaan HPL (High Pressure Laminate) dan Batu Bata sebagai Material Ekonomis dalam Desain Interior Café Tulum Jakarta - Mohammad Lukman Aris Haffif; Tuntun Rahayu (Universitas Krisnadwipayana, Fakultas Teknik Program Studi Arsitektur, 2025)
This study examines the use of High Pressure Laminate (HPL) and exposed brick as economical materials in the interior design of Café Tulum Jakarta. The research methods include field observation, visual documentation, and literature review. The results show that HPL offers design flexibility, easy maintenance, and cost efficiency, while exposed brick provides strong visual character and reinforces local identity. The combination of these materials creates a warm, tropical, and modern atmosphere that enhances user comfort and experience. This study concludes that HPL and exposed brick are effective material solutions for achieving aesthetic, functional, and economical café interior design